People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-IOSCO Objectives and Principles of Securities Regulation-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2014)
This Financial Sector Assessment Program report on People's Republic of China-Hong Kong Special Administrative Region highlights that it has developed a sound framework for the regulation of securities markets, which exhibits a high level of implementation of the International Organization of Securities Commissions Principles. Both the Securities and Futures Commission (SFC) and the Hong Kong Monetary Authority (HKMA) are sophisticated regulators and have been able to leverage from domestic and international expertise to develop sound supervisory practices. Further, while traumatic, the Lehman minibond experience has led to material improvements in conduct supervision that have permeated both the SFC and the HKMA. Continuing efforts by the SFC to build up its capacity to identify and monitor emerging risks should increase the SFC's ability to react in a timely manner to an evolving landscape, marked by an increased interconnection with the Mainland China, an active presence by international players and increased regional competition as an international finance center. It is important to consider translating the operational independence that the regulators have enjoyed into de-jure independence, through modifications in the current legal governance arrangements for both SFC and HKMA.